Ketogenic diet therapy in infants less than two years of age for medically refractory epilepsy. (April 2018) - Ismayilova, Naila; Leung, Mary-Anne; Kumar, Ravi; Smith, Martin; Williams, Ruth E.
Abstract: Purpose: The Ketogenic Diet (KD) is a well-established treatment for epilepsy in children and adults. We describe our 10-year KD experience in children less than two years of age diagnosed with medically refractory epilepsy. Methods: We conducted a retrospective case-note review of infants managed with KD at our centre between 2006 and 2016. Results: Twenty-nine children between 2½ weeks and 23 months of age were identified, with mixed epilepsy aetiologies. Ninety-three percent had daily seizures and 82% were on two or more anti-epilepsy drugs (AEDs) at the time of KD commencement. KD was continued for more than four weeks in 86%. Based on a combination of parental reports, hospital observations and seizure diaries, two of 29 became seizure free, seven demonstrated >50% seizure reduction, and eight showed a decrease in seizure intensity/frequency. No adverse effects were observed in 45% patients, and dietary therapy was stopped in only two because of poor tolerability. Conclusion: We conclude that KD can be utilised and is generally well tolerated in infants with severe epilepsies. In addition, our experience suggests efficacy with improved seizure frequency/severity in around 50% without adverse effects on developmental outcome.